Strengthening square reinforced concrete columns by shape modification and CFRP - Pham, Thong; Doan, L.; Hadi, M. (2013)
A technique called circularization [where segmental, circular, concrete covers made of different concrete strengths (40 MPa, 80 MPa and 100 MPa)] was used to change a square column to a circular column. The behavior of the strengthened specimens under different loading conditions [including concentric loading, eccentric loading (25 mm and 50 mm) and flexural bending] was investigated. The experimental results demonstrate that using high-strength concrete (HSC) for the additional covers to strengthen existing square reinforced concrete (RC) columns provides higher load-carrying capacity than covers made of normal strength concrete. The highest capacity of the strengthened columns was four times higher than that of the corresponding reference column under concentric loading. Theoretical interaction diagrams were established and showed a good agreement with the experimental results.